The use of Arabic loanwords in teaching reading skills from the teachers' perspective - Mainasara, Nasiru; Mohamad, Ab Halim; Hassan, Abdul Rauf; Wan Sulong, Wan Muhammad (Human Resource Management Academic Research Society, 2022)
Previous research findings revealed that students studying Arabic at Umaru Ali Shankafi Polytechnic and Shehu Shagari College of Education Sokoto State, Nigeria, have weak reading ability in the Arabic language. Significantly, which leads us to believe that this issue is real. The study's objectives are to examine the perspectives of Arabic language teachers on the use of Arabic loanwords in the teaching of reading skills and to determine the relationship between the teaching of reading skills with the use of Arabic loanwords and motivating students toward learning Arabic language. The study uses both a descriptive and an inferential quantitative technique. The study sample was made up of (50) teachers of Arabic from the Shehu Shagari College of Education and the Umaru Ali Shinkafi Polytechnic Sokoto. The findings for the first objective established the impact of Arabic loanwords in teaching reading skills to Arabic learners, with the arithmetic mean value ranging between (3.71-4.16). The Spearman correlation coefficient revealed the findings of the second objective which highlighted the positive relationship between the use of Arabic loanwords and encouragement to learn, where the statistical significance came at the level (α = 0.05), which achieves the positive direct relationship from (x) (Arabic loanwords) to (y) encouragement to learning of the Arabic language. In light of the findings, the study recommended employing these loan words in reading skills to Hausa speaker’s learners of the Arabic language.